Associations between post-acute sequelae of SARS-CoV-2, COVID-19 vaccination and HIV infection: a United States cohort study - Yendewa, George A.; Perez, Jaime Abraham; Patil, Nirav; McComsey, Grace A. (Frontiers in Immunology, 2024)
Background: People with HIV (PWH) are at higher risk of complications from acute COVID-19, but their risk of subsequent post-acute sequelae of SARS-CoV2 (PASC) remains unclear. Although vaccination is protective of PASC among survivors in the general population, its effectiveness in PWH has not been explored.We used the TriNetX health research database to identify patients with and without HIV aged ≥18 years with confirmed SARS-CoV-2 between January 1, 2020 and July 20, 2023. We employed 1:1 propensity score matching to balance HIV and non-HIV cohorts based on demographics and key comorbidities. The primary outcomes accessed odds of PASC and mortality and secondary outcomes assessed odds of PASC and mortality by vaccination status. PASC was defined as new-onset conditions ≥ 28 days after COVID-19 diagnosis. We reported odd ratios (OR) of outcomes with 95% confidence intervals (CI), with statistical significance set at p < 0.05.Results: Of 3,029,340 people with confirmed SARS-CoV-2 infection, 0.5% (n=13,214) were PWH, with 7.5% of PWH (n=989) vaccinated. After 28 days post-COVID-19, PWH had higher odds of mortality compared with their non-HIV counterparts (OR 1.22, 95% CI 1.06-1.40) and developing new-onset HTN (OR 1.18, 95% CI 1.03-1.36), heart disease (OR 1.35 95% CI 1.18-1.54), malignancy (OR 1.49, 95% CI 1.22-1.81), and mental disorders (OR 1.62, 95% CI 1.42-1.85). Furthermore, vaccinated PWH had significantly lower odds of death (OR 0.63, 95% CI 0.42-0.93) and new-onset PASC outcomes: DM (OR 0.65, 95% CI 0.43-0.99), heart disease (OR 0.58, 95% CI 0.4-0.85), mental disorders (OR 0.66, 95% CI 0.43-1.00), fatigue (OR 0.82, 95% CI 0.67-0.98), respiratory (OR 0.82, 95% CI 0.70-0.95) and gastrointestinal symptoms (OR 0.78, 95% CI 0.67-0.90).HIV-positive status increased PASC odds, while COVID-19 vaccination reduced PASC and all-cause mortality risks in PWH.